2022
DOI: 10.1002/admi.202101893
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Enhancement of the Electron–Phonon Coupling in Mixed Dimensional CdS/Graphene van der Waals Heterojunction

Abstract: Electron–phonon coupling plays a key role in affecting the properties of the semiconducting nanostructures, such as providing the possibility for obtaining higher superconducting transition temperatures. Here, using Raman, temperature‐dependent and polarized Raman scattering measurements, ultra‐strong electron–phonon coupling in 1D CdS nanowires and 2D graphene heterostructures is demonstrated. The intensity ratio of 2LO/1LO mode in CdS nanowires provides a spectroscopy‐based method to quantify electron–phonon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The increased I 2LO /I 1LO ratio suggests that Ag x @ GSH NCs and Ag NYs play important roles in enhancing excition−phonon coupling in CdS NWs. 30,31 In addition, the signal intensity of Ag x @GSH/CdS and Ag/CdS is much lower than that of the CdS NW substrate, indicative of the successful deposition of Ag x @GSH NCs and Ag NYs on the CdS substrate, thus shielding the CdS signal.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased I 2LO /I 1LO ratio suggests that Ag x @ GSH NCs and Ag NYs play important roles in enhancing excition−phonon coupling in CdS NWs. 30,31 In addition, the signal intensity of Ag x @GSH/CdS and Ag/CdS is much lower than that of the CdS NW substrate, indicative of the successful deposition of Ag x @GSH NCs and Ag NYs on the CdS substrate, thus shielding the CdS signal.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Compared with pristine CdS NWs ( I 2LO / I 1LO = ca 0.53), the intensity ratio of 2LO/1LO in the Ag x @GSH/CdS and Ag/CdS heterostructures is markedly elevated (i.e., 0.71, 0.62, 0.86, and 0.88 for 5-Ag x @GSH/CdS, 5-Ag/CdS, 40-Ag x @GSH/CdS, and 40-Ag/CdS, respectively). The increased I 2LO / I 1LO ratio suggests that Ag x @GSH NCs and Ag NYs play important roles in enhancing excition–phonon coupling in CdS NWs. , In addition, the signal intensity of Ag x @GSH/CdS and Ag/CdS is much lower than that of the CdS NW substrate, indicative of the successful deposition of Ag x @GSH NCs and Ag NYs on the CdS substrate, thus shielding the CdS signal.…”
Section: Results and Discussionmentioning
confidence: 99%
“…So far, numerous researchers have strongly demonstrated that vdWHs based on graphene are the most promising materials for potential applications in electronic and optoelectronic fields. Generally, graphene could form various vdWHs with zero-dimensional (0D) quantum dots and plasmonic nanoparticles such as Ag nanoparticles [10,11], one-dimensional (1D) nanoribbons and nanowires such as CdS nanowires, carbon nitride sheet [12,13], as well as two-dimensional (2D) nanomaterials such as hexagonal boron nitride, layered transition metal dichalcogenides and metal oxides [14][15][16][17][18][19][20][21], referred to as 0D-G, 1D-G, and 2D-G vdWHs, respectively. Especially, the 1D-G vdWHs have already been used to fabricate many transistors with high speed and flexibility by using the 1D structure as a gate [22,23].…”
Section: Introductionmentioning
confidence: 99%